Effect of wheat sprout powder incorporation on lipid oxidation and physicochemical properties of beef patties - Ozturk, Ismet; Sagdic, Osman; Tornuk, Fatih; Yetim, Hasan (WILEY, 2014)
The aim of this study was to determine the effects of incorporation of wheat sprout flours (WSF) on lipid oxidation and some quality characteristics of beef patties. Two wheat sprout flour samples (WSF1 and WSF2) were obtained by germination, drying and milling of two different wheat varieties. The beef patties were stored at +4 degrees C for 6days or at -18 degrees C for 180days and analysed for their proximate composition, pH, sensory properties, colour parameters and lipid oxidation. TBA formation in WSF-added patties was reduced approximately by as much as 20% when compared to that of the control at the 180th day of the storage, while favourable results were detectable in the storage period at +4 degrees C. Again, up to 4% WSF1 or WSF2 incorporation gave acceptable sensorial scores to the beef patties. As a conclusion, it was confirmed that WSF could be incorporated into beef patties to improve their quality parameters and retard lipid peroxidation.
Keywords: Beef patty; lipid oxidation; storage; thiobarbituric acid; wheat sprout powder; FATTY-ACID-COMPOSITION; VITAMIN-E; QUALITY CHARACTERISTICS; ANTIOXIDANT ACTIVITY; ALPHA-TOCOPHEROL; LEGUME FLOURS; STABILITY; MEATBALLS; IRRADIATION; IMPROVEMENT; Food Science & Technology